Noninvasive Fluorescent Imaging Reliably Estimates Biomass In Vivo. (December 2002) - Diehn, F.E.; Costouros, N.G.; Miller, M.S.; Feldman, A.L.; Alexander, H.R.; Li, K.C.P.; Libutti, S.K.
Whole-body optical imaging of small animals has emerged as a powerful, user-friendly, and high-throughput tool for assaying molecular and cellular processes as they occur in vivo. As with any imaging method, the utility of such technology relies on its ability to provide quantitative, biologically meaningful information about the physiologic or pathologic process of interest. Here we used an animal tumor model to evaluate the extent of correlation between noninvasively measured fluorescence and more traditional measurements of biomass (tumor volume and tumor weight). C57/BL6 mice were injected subcutaneously with murine colon adenocarcinoma cells that were engineered to express GFP. Serial measurements of fluorescence intensities were performed with a macroscopic in vivo fluorescence system. The progressive increases in intensity correlated strongly with growth in tumor volume, as determined by caliper measurements (R 2 = 0.99). A more stringent correlation was found between fluorescence intensity and tumor weight (R 2 = 0.97) than between volume and weight (R 2 = 0.89). In a treatment experiment using tumor necrosis factor-α, fluorescence intensity (but not tumor volume) was able to differentiate between treated and control groups on day 1 post-treatment. These results validate the ability of noninvasive fluorescent imaging to quantify the number of viable, fluorescent cells in vivo.